Conceptual framework for facilitating reflective practice by nurses in the clinical setting - Nelumbu, Lucia; Pretorius, Louise (International Journal of Advanced Nursing Studies, 2015)
Problems or incidents occurring in clinical settings are often seen as indicators of poor nursing care and even indicators of a lack of reflective practice skills. This paper presents the description of the conceptual framework to facilitate reflective practice for registered nurses in clinical settings. It focuses on the characteristics of the agent (lecturer as a facilitator) and recipients (registered nurses), the context of the clinical practice, the procedures for the facilitation of reflective practice and the terminus or the outcome of reflective practice as may they be demonstrated by quality nursing care for patients.